2018
DOI: 10.11160/bah.101
|View full text |Cite
|
Sign up to set email alerts
|

Where to live in Lisbon: urban habitat used by the introduced Italian wall lizard (<em>Podarcis siculus</em>)

Abstract: Exotic animal invasions constitute a major threat to biodiversity worldwide. Once the Italian wall lizard (Podarcis siculus) was accidentally introduced in Lisbon (Portugal) two decades ago, the present assessment determined the core range occupied by this alien lizard in the urban area of Parque das Nações. Despite the apparent current scenario of non-expansion, the alien species interferes with the local distribution pattern of the native P. virescens, with both lizard species shown to use the available micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…The amount of niche overlap, and hence, interspecific interactions, between the invasive lizards and the native lizard is still not entirely known. Our observations suggest that the invasive lizards are displacing the native fence lizards at each site because the fence lizards are absent from the core of the invasives’ distributions (where they once occurred), a pattern consistent with other observations of native-invasive lizard interactions ( Ribeiro and Sá-Sousa 2018 ). However, because of the little overlap between the 2 species’ distributions, it is unlikely that the differences in behaviors we recorded for this study are the direct result of interspecific competition/aggression.…”
Section: Discussionsupporting
confidence: 88%
“…The amount of niche overlap, and hence, interspecific interactions, between the invasive lizards and the native lizard is still not entirely known. Our observations suggest that the invasive lizards are displacing the native fence lizards at each site because the fence lizards are absent from the core of the invasives’ distributions (where they once occurred), a pattern consistent with other observations of native-invasive lizard interactions ( Ribeiro and Sá-Sousa 2018 ). However, because of the little overlap between the 2 species’ distributions, it is unlikely that the differences in behaviors we recorded for this study are the direct result of interspecific competition/aggression.…”
Section: Discussionsupporting
confidence: 88%
“…The Italian wall lizard Podarcis siculus is an endemic lacertid of the Italian peninsula and the Adriatic basin and an efficient invasive species in other European and not European countries ( Burke et al, 2002 ; Ribeiro and Sá-Sousa, 2018 ; Damas-Moreira et al, 2019 ). This lizard is dorsally green-brown for most of its activity period (March to October) and males especially show a green to azure gular region at the peak of their reproductive season ( Corti et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such barriers may include spatial segregation between the two host species, immunological differences, or transmission vector affinity towards a specific host species (Poulin 2017 ). It is unlikely that spatial segregation promotes differences in parasite infection given it would occur across a micro-scale and that the two host species can punctually overlap in Lisbon (Ribeiro and Sá-Sousa 2018 ). On the other hand, immunological differences between the two species might be supported by the low parasite intensity in P. siculus , both in Lisbon and in Tuscany.…”
Section: Resultsmentioning
confidence: 99%
“…Podarcis virescens is a native species of the Iberian Peninsula, which occupies central Spain and southern Portugal (Geniez et al 2014 ) and has no reported introductions elsewhere. These two lizard species have overlapping habitat and presumably similar dietary preferences (Arnold and Burton 2002 ; Ribeiro and Sá-Sousa 2018 ), and therefore compete for similar resources. In Lisbon, the two lizards occur in sympatry, and present differences in their behaviour and competition skills (Ribeiro and Sá-Sousa 2018 ; Damas-Moreira et al 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation